MODERNISASI PENDIDIKAN ISLAM PERSPEKTIF AZYUMARDI AZRA DALAM BUKU PENDIDIKAN ISLAM TRADISI DAN MODERNISASI DI TENGAH TANTANGAN MILENIUM III - Azim, Fauzan; Chanifudin, Chanifudin; Ritonga, Supardi (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research is a series of activities carried out systematically and planned to solve a problem. This type of research uses descriptive content analysis and text study with the character of library research (library research). In this research, the researcher discusses the Modernization of Islamic Education from Azyumardi Azra's Perspective in the Book of Traditional Islamic Education and Modernization in the Middle of Millennium III Challenges. According to Azyumardi Azra, education is based on self-devotion to Allah, which is useful for oneself, society and nature. The implementation of Islamic education thought was initiated by Azyumardi Azra who stated that Islamic education is not just a transfer of knowledge but also a system that is structured on the basis of a strong faith and in carrying out the goals of Islamic education must be aligned with the basics and characteristics ideally as well as a curriculum that is in accordance with the system. education